2009
DOI: 10.1124/dmd.109.030254
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Rate-Determining Process in the Hepatic Elimination of HMG-CoA Reductase Inhibitors in Rats and Humans

Abstract: ABSTRACT:Elucidation of the rate-determining process in the overall hepatic elimination of drugs is critical for predicting their intrinsic hepatic clearance and the impact of variation of sequestration clearance on their systemic concentration. The present study investigated the rate-determining process in the overall hepatic elimination of the HMG-CoA reductase inhibitors pravastatin, pitavastatin, atorvastatin, and fluvastatin both in rats and humans. The uptake of these statins was saturable in both rat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(156 citation statements)
references
References 36 publications
12
144
0
Order By: Relevance
“…Renally eliminated compounds that are substrates for P-gp, which is present in both the liver and kidney among many other tissues, might not be substrates for hepatic uptake transporters, and are therefore not biliarily accessible. As others have hypothesized, hepatic uptake, particularly by OATPs, may be a rate-limiting step in biliary excretion (5,8). Indeed, acrivastine and levocetirizine were not found to be substrates of major hepatic uptake transporters in the literature.…”
Section: Importance Of Metabolic Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Renally eliminated compounds that are substrates for P-gp, which is present in both the liver and kidney among many other tissues, might not be substrates for hepatic uptake transporters, and are therefore not biliarily accessible. As others have hypothesized, hepatic uptake, particularly by OATPs, may be a rate-limiting step in biliary excretion (5,8). Indeed, acrivastine and levocetirizine were not found to be substrates of major hepatic uptake transporters in the literature.…”
Section: Importance Of Metabolic Stabilitymentioning
confidence: 99%
“…While human liver microsomes generally provide reliable predictions of human metabolic clearance for extensively metabolized drugs (8)(9)(10)(11)(12)(13) and renal clearance is not difficult to determine, predictions of human biliary clearance are difficult and scarce, despite ongoing efforts (14). Clinical methods include bile duct cannulation during surgery, collection of duodenal fluid in healthy volunteers, or fecal collections.…”
Section: Introductionmentioning
confidence: 99%
“…All of these results suggested that the enhanced activity and expression of hepatic Cyp3a were the main contributors to the increases in systemic clearance of simvastatin and simvastatin acid. The uptake of drugs by hepatocytes is also considered a rate-determining process in the hepatic clearance of statins via OATPs [33,34] . The uptake of simvastatin by hepatocytes and the expression of Oatp2 were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of simvastatin by hepatocytes Uptake of statins by hepatocytes is considered a ratedetermining process in the overall hepatic elimination of statins [33,34] . The uptake of simvastatin by hepatocytes was investigated using freshly isolated rat hepatocytes from experimental rats ( Figure 3D).…”
Section: Pharmacokinetics Of Simvastatin In Dm Rats After Oral and Inmentioning
confidence: 99%
“…19) Regarding statins, Watanabe et al have demonstrated that the overall hepatic clearance of 4 statins, pitavastatin, rosuvastatin, atorvastatin and fluvastatin is mainly dominated by the hepatic uptake process. 20) Pitavastatin and rosuvastatin are not metabolized in rats and mainly excreted into bile in an unchanged form, whereas atorvastatin and fluvastatin, which are both reported to be OATP substrates, are extensively metabolized by CYP3A4 and CYP2C9, respectively. In vivo hepatic clearances of these statins were well correlated with in vitro uptake intrinsic clearances obtained with isolated hepatocytes, but poorly correlated with in vitro metabolic intrinsic clearances obtained with liver microsomes.…”
Section: Ps CL β Ps Ps Clmentioning
confidence: 99%